2014
DOI: 10.4236/ojf.2014.41011
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Firewood Scarcity in Soroti District of Eastern Uganda

Abstract: This study investigated how rural households cope with firewood scarcity in dryland areas of Eastern Uganda. A household survey was conducted in December 2008 to January 2009, where 490 respondents were randomly interviewed. Focus Group Discussions (FGDs) were also held with community elders and women. Responses were analyzed both descriptively and qualitatively. Findings indicated that 99% of the households used firewood for cooking with a per capita consumption of 542.32 Kilograms. Commonly used tree species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
10
1
1
Order By: Relevance
“…Gliricidia species is a promising candidate for establishment of such planation as it is the most common species in the study site ( Table 3 and Table 5). Even though Acasia, Mango and Cashew trees are used as fuelwood in tropical areas of the world [29], end users preference of these three species in our study were found to be low because of low calorific values and negative effect on the quality of the end product, i.e. tea.…”
Section: Discussioncontrasting
confidence: 59%
“…Gliricidia species is a promising candidate for establishment of such planation as it is the most common species in the study site ( Table 3 and Table 5). Even though Acasia, Mango and Cashew trees are used as fuelwood in tropical areas of the world [29], end users preference of these three species in our study were found to be low because of low calorific values and negative effect on the quality of the end product, i.e. tea.…”
Section: Discussioncontrasting
confidence: 59%
“…The lower opportunity cost associated with accessing firewood from the forest reserve could explain the observed fuel sourcing behaviour there. Forest reserves are associated with sufficiency (Kandel et al, 2016), quality and diversity of firewood (Egeru et al, 2014;Agea et al, 2010). Availability of labour is another factor that could drive households to assign more effort to energy sourcing.…”
Section: Heterogeneity In Socio-economic and Biomass Energy Characteristics Among Cluster Sub-countiesmentioning
confidence: 99%
“…Despite the plethora of studies, information gaps exist in relation to incorporating agricultural crop production systems and bio-energy into household energy choice (Popp et al 2014). Notably, this happens in a situation where bio-energy crops (Soto, et al 2018) and tree planting for domestic energy subsistence (Agea et al 2010;Egeru et al 2014) have become agricultural activities. Desegregating cooking energy choice by meal types can provide further insights into households' energy demand (Muller and Yan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gender and age play an important role in determining the susceptibility to damage caused by adverse effects of climate change. As noted above, the fact that women in many countries are tasked with collecting water and firewood means that they are more susceptible to damages from climate hazards (Egeru, et al, 2014 andIPCC 2014, p. 796). 6 Sherwood (2013) finds that prolonged drought created poverty traps for women in Gituamba, Kenya.…”
Section: Gender and Age Inequality And Susceptibilitymentioning
confidence: 99%